Financial Health Assessment of Bank BRI: Trends in Liquidity, Profitability, and Management Efficiency - Riu, Isma Azis (Abadi Institute, 2024)
Banking is the backbone of the construction of Indonesia's economic and financial system. A variety of economic issues greatly affect the business world, especially banking, where companies compete to perform well. Several metrics can be used to assess a bank's financial performance, such as the bank's financial statement performance. Financial reports are one of the information media that can provide an overview of a bank's health. The purpose of this study is to